Dynamic Display Design of Cultural and Creative Products Based on Digital Augmented Reality Technology - Zhuoran Zhang (Mobile Information Systems, 2022)
The development of science and technology has brought about a change in life, and this has also caused people to use technology more and more frequently. In the dynamic display design of cultural and creative products, people are also beginning to look for a technology that can better deal with it. Its characteristics are displayed, which is the research of this article. This article aims to study how to carry out a dynamic display design for cultural and creative products. To this end, this paper proposes a method of digital augmented reality technology, optimizes the visual search technology in augmented reality technology, studies and analyzes its specific digital implementation process, divides and understands the technical principles, and designs relevant experiments to study its specific display effect and carry out the relevant effect analysis in the analysis part. The experimental results of this article show that the improved augmented reality technology can better enhance the consumer’s interactive experience. At the same time, the consumers’ purchase intentions have also been improved by 43%. It can be said that the dynamic effects of cultural and creative products are well demonstrated.